Efektivitas Sistem Informasi Administrasi Kependudukan Online (Sihobas. Online) Di Dinas Kependudukan Dan Pencatatan Sipil Kabupaten Simalungun - Muhammad Surya Ramadhan; Februati Trimurni (UNIVED PRESS, Universitas Dehasen Bengkulu, 2022)
Citizens fell difficult to access Sihobas. Online services which should make it easier to take care of the required population documents. The purpose of this study was to describe the effectiveness of the Population Administration Information System (Sihobas. Online) at the Simalungun Regency Population and Civil Registration Service. This study use a qualitative descriptive research method. The data obtained were then analyzed using the Martani and Lubis theoretical approach, which focused on the process approach as viewed from Human Resources, Facilities and Infrastructure and Population Documents. Through this research, it is known that Sihobas. Online is not running effectively, this is because currently Sihobas. Online is not activated and cannot be accessed by the public in an indefinite period of time.